Estoque de carbono e nitrogênio em terra preta e terra mulata na reserva biológica do Rio Trombetas, Oriximiná/PA - Araújo, Cauan Ferreira (Instituto Nacional de Pesquisas da Amazônia - INPA, 2020)
The research summarized here aimed to estimate the stock of carbon and nitrogen in patches of Terra preta on function plots determined by thickness categories of anthropogenic A horizon. To this end surveys were conducted at three sites in the Biological Reserve of the Rio Trombetas region trough - north city of Oriximiná/PA. The spatial distribution of anthropogenic A horizon thickness in each spot was determined by polls, semiregular grid of 25m x 25m, and geostatistical interpolation method of ordinary kriging interpolation . Soil sampling was conducted in plots of 10m x 10m, with three replicates for each thickness category of anthropogenic A horizon in increments 0 - 10cm, 10 -20cm, 20 - 50cm, 50 - 100cm. The relationship Carbon total: Total nitrogen was determined by dry combustion. The Kriging thickness anthropogenic A horizon obtained better results with the model Theoretical exponential. It has been demonstrated that the three sites have a depth similar, indicating possibly contemporary settlements. The results indicate that the sites have stocks of C and N in the first meter of soil than those found in soils adjacent immediate, reaching averages of 293.37 t C ha-1 and 149.17 t ha-1 N, and 219, 33 t C ha-1 and 121.30 t ha-1 N in Terra Preta and Terra Mulata, respectively. The C: N ratio was significantly higher in the subsurface layers of both sites classified as Terra Preta, Terra Mulata but not in. Therefore, it is concluded that the terms Terra Preta and Terra Mulata keep distinct anthropogenic processes that result in different subsurface conditions. The division of plots tended to differentiate the plot thickened as opposed to the soil less thick and the ground immediately adjacent to stocks as C, N. both models indicating that anthropogenic "bin" and "farm" to show behaviors associated spatial deposition nuclei.